Keadilan Pemilu dalam Kampanye Pilkada Pada Pasangan Calon Tunggal Tahun 2020 di Kabupaten Pasaman - Ahmad Suhendra; Khairul Fahmi (Mahesa Research Center, 2024)
This article aims to examine the portrait and fairness of elections in the implementation of campaigns in regional head elections with a single-candidate pair and provide suggestions for the design of campaign implementation rules. This research focuses on electoral fairness in the implementation of the campaign in the 2020 regional head election for each pair of candidates in Pasaman Regency. The research method used a juridical-empirical method that examines existing law and reality. Data collection was through literature reviews such as primary data, and interviews using the purposive sampling method which took into account the characteristics of the sample. This research was a qualitative analysis which described and arranged systematically. This study concludes that there are legal gaps in KPU regulations governing the procedures and distribution of campaign materials to the public. This happened after there was a report of a violation from the public who questioned the legality of volunteers placing campaign props in the form of banners in empty rows, and journalists asked for the banners to be removed. Responding to this violation, the Pasaman Regency Bawaslu determined that the report did not constitute a violation because the empty column did not violate any provisions. The existence of a legal vacuum has an impact on the emergence of gaps in voters' rights in terms of access to information, and the gap between single candidate pairs and empty columns in conducting election campaigns has not been fulfilled.